CP-222 Does the impact of opioid induced constipation differ by type of chronic pain?. (14th February 2016) - Datto, C; LoCasale, R; Wilson, H; Coyne, K
Abstract : Background: Opioids are often recommended by guidelines for the treatment of various types of chronic pain. Opioid treated patients with chronic non-cancer pain report 40–80% prevalence of opioid induced constipation (OIC), and the presence of OIC negatively impacts health related quality of life (HRQL). OIC's impact on different chronic pain types is unknown. Opioids can intensify constipation, compounding the interdependent relationship between constipation and back pain. Purpose: To examine OIC's impact on patients with chronic back pain versus other chronic pain types. Material and methods: Adult chronic non-cancer pain patients receiving daily opioids for ≥4 weeks and reporting OIC participated in a 24 week prospective longitudinal study. Web based surveys at baseline and at weeks 2, 4, 6, 8, 12, 16 and 24 assessed OIC symptoms, laxative use, pain level, HRQL, productivity and perceived satisfaction with laxatives. Patients were asked about constipation symptom frequency and the bother associated with each reported symptom. Results: 489 eligible patients reported back pain only (BP: n = 89, 18.2%), back pain+other pain (BPOP: n = 286, 58.5%) or other pain only (OP: n = 114, 23.3%). Abdominal discomfort, abdominal pain, stomach cramps, rectal burning and bowel movements (BMs) too hard were reported to occur with >25% of BMs more frequently among BP than OP. BP reported significantly greater bother with abdominal pain, bloating, stomach cramps and painful BMs than OP. Significantly greater HRQL impact was observed among BP than OP. BP reported the highest rates of laxative non-use (39.3%) and were more likely to report little benefit from laxatives (71%) than the other groups. Conclusion: Patients with BP reported significantly greater OIC symptom frequency, bother and HRQL impact than patients with OP. High rates of laxative non-use among patients with BP likely contributed to their higher OIC symptom burden. Whether better information about effective OIC therapies will reduce OIC burden or patients eschew current therapies due to tolerability issues or lack of efficacy requires further exploration. Clinician-patient conversation is warranted, and patients with BP and OIC require additional attention. References and/or Acknowledgements: Funding for this research was provided by AstraZeneca Pharmaceuticals LP (Wilmington, DE, USA). Conflict of interest.